Pengaruh Literasi Keuangan Terhadap Manajemen Keu-angan Pedagang di Pasar Tradisional - Ahmad Haekal Munzir Aminuddin; Samsul Bachri; Abid Ramadhan (Pusat Riset dan Inovasi Nasional, 2025)
One of the common issues encountered in traditional markets is the low level of financial literacy among traders. This condition affects the suboptimal management of business finances, as reflected in disorganized financial records, difficulties in separating business and personal funds, and a lack of preparedness in dealing with financial risks. This situation frequently occurs among traders in traditional markets, where the majority still manage their finances in a simple manner, without a proper recording system, and lack understanding of the importance of financial planning, debt management, and efficient capital allocation. This study aims to examine the influence of financial literacy on the financial management of traders in traditional markets. The research method used is quantitative with a survey approach, collecting data through questionnaires distributed to traders in the market. The sample was selected using purposive sampling technique, with a total of 66 respondents. Data analysis was conducted using descriptive statistics, validity and reliability tests, normality test, and simple linear regression, assisted by IBM SPSS 20 software. The results of the study show that financial literacy has a positive and significant effect on the financial management of traders in the market. It is expected that the findings of this research can contribute to the management of Padang Sappa Market and the local government in improving financial management among traditional market traders.